Type I interferons in inflammatory bowel diseases: balancing barrier integrity, repair and inflammation in the intestinal epithelium - King, Mikayla R.; Kemp, Roslyn A.; Gadeock, Safina (Frontiers in Medicine, 2025)
Inflammatory bowel diseases (IBD), including Crohn’s disease and ulcerative colitis, are persistent, relapsing immune mediated disorders of the gastrointestinal tract associated with significant morbidity and considerable health-care costs. Current therapeutic strategies, such as corticosteroids, immunomodulators, and biologic agents including anti-tumour necrosis factor (anti-TNF) therapies, provide a clinical advantage; however, there is a 30–40% primary non-response rate followed by a 50% secondary non-response rate. This highlights the need for novel therapeutic targets that can specifically address patient heterogeneity. Type I interferons (IFN-Is) are broad acting cytokines that apply state-dependent effects on epithelial intestinal homeostasis. At normal biological levels, IFN-Is reinforce epithelial barrier integrity by regulating tight junction formation, epithelial turnover, and antiviral defence mechanisms. However, in IBD, dysregulated IFN-I signalling facilitates atypical immune cell recruitment, epithelial apoptosis, and prolonged epithelial cell inflammation. The impact of IFN-Is on the dysregulation of the epithelial barrier in IBD remains poorly understood. Patient-derived intestinal organoids represent a physiologically relevant model that aids in the understanding of IFN-I signalling pathways in epithelial cells, allowing for adequate studies on the epithelial–immune crosstalk phenomenon in IBD. This review identifies and highlights IFN-Is as a promising but context-dependent therapeutic target. Interpreting the molecular mechanisms of IFN-Is and their role on the intestinal epithelial barrier function will benefit our understanding of treatment responsiveness as well as aid in resolving current therapeutic challenges in IBD.